TINGKAT KEIKUTSERTAAN MASYARAKAT DALAM PROSES PEMBENTUKAN UNDANG-UNDANG - Eny Susilowati (Fakultas Hukum Universitas PGRI Palangkaraya, 2017)
Abstract : Community participation in a process of formulating laws, local regulations and other legislation has an important meaning for the birth of a quality legal product. It can be observed in the Law arising from non-participatory processes, at least 4 (four) categories of Laws arising from non-participatory processes: 1) Such laws or regulations are ineffective, in the sense that they can not achieve the objectives expected, 2) The law or regulation is not implementation, in the sense that it can not be executed since it is enacted or fails early; 3) Unresponsive laws or regulations, which have since been drafted to the point of getting strong rejection from the public; and 4) Laws or regulations that instead of solving social problems cause new difficulties in society, they are ineffective, in the sense of not being able to achieve the intended objectives. Keywords : Community participation, process, Undang-undang